2007
DOI: 10.1111/j.1365-2702.2006.01824.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐synthesis of caring in nursing

Abstract: The findings explicate a cohesive process of caring. They provide insight into the human attributes and clinical milieu that are necessary for caring to emerge. They also offer clarity regarding the therapeutic benefits of caring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
254
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(273 citation statements)
references
References 54 publications
7
254
0
12
Order By: Relevance
“…Although, in our study, the priority was given to physical needs of patients, however, this aspect of care sometimes were neglected. Price [25], Andersson et al [1] and Fingfeld-Connett [22] found out that caring grounded in its context and affected by culture of the unit and work pressures on the stuff, so, the default is attributable to heavy workload, staff shortage, and lack of knowledge regarding proper use of some technological tools, in the specific context of the present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although, in our study, the priority was given to physical needs of patients, however, this aspect of care sometimes were neglected. Price [25], Andersson et al [1] and Fingfeld-Connett [22] found out that caring grounded in its context and affected by culture of the unit and work pressures on the stuff, so, the default is attributable to heavy workload, staff shortage, and lack of knowledge regarding proper use of some technological tools, in the specific context of the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Nascimento and Erdemann [2] stated that caring makes a sense of harmony between self and the environment, in care provider and the person who received it. Fingfeld-Connett [22] argued that creating an intimate atmosphere which facilitates exchange of feelings and emotions between nurse, patient, and family, makes a sense of calm and comfort in the nurse and patient and stated that nurses' 'mental well-being is an outcome for caring. These findings are consistent with our study participants' explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Caring is an interpersonal interaction that is part of being human (Finfgeld-Connet, 2008; McCormack & McCance, 2010), and the professional’s main responsibility in encounters with patients and their families is to be caring. However, such caring may be constrained by nurses’ own insecurities and perceptions of older people’s attitudes towards death; nurses might avoid discussing existential issues and death in an effort to avoid reinforcing a patient’s feeling of hopelessness (Udo, Danielson, & Melin-Johansson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…En la literatura esa disposición para el cuidado es una condición conformada por un personal abierto, con sensibilidad interpersonal y pacientes necesitados de cuidado por enfrentarse al procedimiento quirúrgico (49,50,51).…”
Section: Resultsunclassified